2007
DOI: 10.1007/s11274-007-9427-2
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid preference of mycelium-bound lipase from a locally isolated strain of Geotrichum candidum

Abstract: Mycelium-bound lipase (MBL) was prepared using a strain of Geotrichum candidum isolated from local soil. At the time of maximum lipase activity (54 h), the mycelia to which the lipase was bound were harvested by filtration and centrifugation. Dry MBL was prepared by lyophilizing the mycelia obtained. The yield of MBL was 3.66 g/l with a protein content of 44.11 mg/g. The lipase activity and specific lipase activity were 22.59 and 510 U/g protein, respectively. The moisture content of the MBL was 3.85%. The act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…In contrast, the cell-bound lipase possesses selectivity to saturated fatty acids. A similar finding was observed when the mycelium-bound lipase from G. candidum (IMI 387428) was used as a biocatalyst during hydrolysis of palm olein (Loo et al, 2007). The lipase showed selectivity for oleic acid over palmitic acid, indicating that it displayed high substrate selectivity for unsaturated fatty acid containing a cis-9 double bond, even in crude form.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…In contrast, the cell-bound lipase possesses selectivity to saturated fatty acids. A similar finding was observed when the mycelium-bound lipase from G. candidum (IMI 387428) was used as a biocatalyst during hydrolysis of palm olein (Loo et al, 2007). The lipase showed selectivity for oleic acid over palmitic acid, indicating that it displayed high substrate selectivity for unsaturated fatty acid containing a cis-9 double bond, even in crude form.…”
Section: Resultssupporting
confidence: 74%
“…Although they have attracted great attention, as can be seen from the many previous works (Loo et al 2007;Song et al 2008), it is still necessary to add more interesting and helpful information on the specificities of lipases, especially those lipases from different microorganisms. Triacylglycerols, fatty acid methyl esters and p-nitrophenyl esters were used as substrates in lipase hydrolysis trials.…”
Section: Resultsmentioning
confidence: 99%
“…The concentrations used vary greatly, but the range from 0.1 to 5.0 % w/w is more commonly used, and organic sources are added in higher quantities than inorganic sources . Concentrations (% w/w) of: 5.0 of peptone; 2.0 of yeast extract and 0.1 of NaNO 3 and 0.5 of NH 4 NO 3 are commonly applied in the lipase production [43][44][45][46]49,57 ; however, optimized studies about medium composition reduced or eliminated some nitrogen sources in the process. Burket et al and Maldonado et al showed that 3.58 % w/w of peptone is enough to obtain a high level of lipase activity from G. candidum.…”
Section: Production Of Geotrichum Spp Lipasesmentioning
confidence: 99%
“…The inoculum is another important variable in the lipase production from Geotrichum, and the liquid form 45,46 , used at 10 % (v/v) 47 or 5 % (v/v) 48 , is frequently applied. However, this type of inoculum can be an obstacle to the homogenization and standardization of inoculum, as shown by Resende-Maldonado et al 49 The authors proposed the utilization of an initial solid inoculum (with a specific area) followed by an intermediate liquid inoculum that reduced the variability of the lipase activity by 33 % during the fermentation.…”
Section: Production Of Geotrichum Spp Lipasesmentioning
confidence: 99%
See 1 more Smart Citation